Development of a 325 MHzβ=-0.12 superconducting single spoke cavity for China-ADS - 李菡 戴建枰 沙鹏 王群要 黄泓 李黎海 张娟 马强 林海英 孙毅 潘卫民 (Chinese physics C, 2014)
Twelve very low Beta superconducting single spoke cavities, whose Beta is only 0.12 （Spoke012） when operating at 325 IvIHz, are adopted in Injector I for China-ADS linac. This type of spoke cavity is believed to be one of tile key challenges for its very low geometric Beta. So far, in collaboration with Peking University and Harbin Institute of Technology, IHEP has successfully designed, fabricated, and tested the Spoke012 prototype cavity. This paper presents the details of the design, fabrication and test results for Spoke012 prototype cavity.